Tell me your socially responsible practices, I will tell you how attractive for recruitment you are!: the impact of perceived CSR on organizational attractiveness - Duarte, A. P.; Gomes, D.; Neves, J. (Tékhne - Review of Applied Management Studies, 2014)
This experimental study seeks to extend the current knowledge about the impact of corporate social responsibility on organizational attractiveness by analyzing the mediating role of corporate image. To the best of our knowledge, no study has empirically tested this. Participants (n = 195) randomly received an individual survey containing a description of a company as fulfilling (high engagement condition) or not fulfilling (low engagement condition) a set of socially responsible practices, followed by questions about the study variables. Structural equation modeling analyses revealed that the proposed model has a strong fit to the data, evidencing that the perceived level of engagement in socially responsible practices contributes to triggering the process that leads individuals to evaluate an organization as a good place to work. Corporate social responsibility can thus be a source of competitive advantage regarding the recruitment of new employees. Accordingly, information related to corporate social performance should be considered by recruiters.